Civic journalism narrating violence in Mexico. Interview with Marcela Turati (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
The paper, reporting the interview with Mexican journalist Marcela Turati, deals with issues related to the spread of extreme violence in Mexico since 2006 and the related institutional narration; the development of innovative forms of journalism as a reaction to the spreading of violence; and, finally, the engagement of local women journalists in defending human rights, as well as the feminist network sheltering them.
Keywords: civic journalism; Mexico; organized crime; Marcela Turati; human rights